Transformation of Islamic Education Learning Models Through a Constructivist Approach - Mohammad Syaifuddin; Moh. Muslih; Arif Chasanul Muna; Nur Khikmah; Arditya Prayogi (ISTIFHAM, 2026)
This study describes the transformation of the Islamic Religious Education (PAI) learning model through a constructivist approach at SMP Negeri 1 Pekalongan. The study departs from the persistence of lecture-oriented, memorization-based PAI learning, which often limits students' opportunities to construct meaning, discuss religious values, and connect Islamic teachings to daily life as Gen Alpha learners. A qualitative case study design was used, with two PAI teachers as the only informants, purposively selected because they directly design and implement PAI learning. Empirical data were enriched through in-depth interviews with the two teachers, classroom observations, and documentation of teaching modules, learning activities, and student learning products. The data were analyzed using Miles and Huberman's interactive model through data condensation, data display, and conclusion drawing, while validity was strengthened through technique triangulation, member checking, and peer discussion. The findings show three main forms of transformation: a gradual shift from teacher-centered explanations to guided, student-centered learning; the use of cooperative, project-based, and problem-based learning, as well as inquiry, in selected PAI materials; and stronger student participation, collaboration, and reflective understanding of Islamic values. The implementation remains constrained by limited time, heterogeneous student readiness, classroom management demands, and the need for more consistent reflective assessment. This study confirms that constructivism is relevant for contextual and value-oriented PAI learning when guided by clear Islamic educational objectives.